Modern trends in Islamic theological discourse in 20th century Indonesia : a critical study - Saleh, Fauzan (Social, economic, and political studies of the Middle East and Asia ;, 2001)
Annotation "Aiming to trace the development of Islamic theological discourse in Indonesia from the early 1900s to the end of the 20[superscript th] century, the author focuses on how modernist Muslims have constructed their theological thought throughout the century, which, in turn, reflects their religious understanding in response to the particular demands of their age. The theological thought constructed so far signifies a continuum of progress, developing from one stage to the next. Implicitly, this progress also indicates the improvement of Indonesian Muslims' understanding of their own religion, which may suggest the betterment of their commitment to doctrinal beliefs and religious practices. Therefore, this study will also examine the ways in which Indonesian Islam noticeably grows more orthodox through these forms of religious commitment. Drawing upon an Indonesian term, the growth of orthodox Islam is known as the santri cultural expansion, which has been characterized by the vertical and horizontal mobility of devout Muslims in political, cultural and economic enterprises. A discussion of the theological thought underlying that santri cultural expansion is also included."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved